Clinical study of the correlation of foot length and birth weight among newborns in a tertiary care hospital - S., Gowri; V., Kumar G. (International Journal of Contemporary Pediatrics, 2017)
Background: Gestational age and birth weight are the two most useful parameters for assessing maturity of the newborn. Major causes of neonatal mortality are diseases associated with low birth weight babies (LBW). It has been shown that foot length measurement is particularly valuable in premature babies who are so ill that conventional anthropometric measurements cannot be carried out due to the incubator and intensive care apparatus. Methods: The cross-sectional study was conducted in the department of pediatrics Sri Siddhartha Medical College Hospital, Tumkur, India. The birth weight in grams and length of the foot were documented in centimeters. Data was collected using standard proforma. Results: A total of 600 neonates were studied of which, males were 54.67 % (328) and females were 45.33 % (272). The neonates weighing less than 2.5 kg had a mean foot length of 6.94. The mean foot length for neonates weighing between 2.5 to 3.5 was 7.68. The mean foot length for neonates weighing more than 3.5 kg was 8.2cm. The correlation coefficient of birth weight with foot length was maximum in low birth weight babies (r= 0.94). Conclusions: The foot length is an efficient screening tool in identifying low birth weight babies. Foot length is a simple, quick and reliable anthropometric measurement which can be used as a proxy measurement to birth weight especially in sick and pre-term neonates receiving intensive care.